Compliance with the surgical safety checklist in a hospital in Santander. A cross-sectional study - Sepúlveda Plata, Martha Cecilia; Lopez Romero, Luis Alberto; González, Sandra Beatriz (Revista Cuidarte, 2021)
Introduction: Patient safety constitutes a priority in health care, being the surgical safety checklist one of the strategies implemented by the WHO. The objective was to determine the level of compliance in the application of the surgical safety checklist in surgical room personnel of a public institution. Materials and Methods: Cross-sectional study in 45 members of the surgical team in a hospital, in which compliance to the WHO checklist was evaluated during July and August 2018. Results: Overall compliance was 13.3% (n=6), with the pre-anesthesia phase reaching the highest level (55.6%, n=25). The highest compliance was recorded by the surgical instrumentation staff (100%, n=8), while the lowest by the nursing staff (25%, n=3), with statistically significant differences (p=0.005). Additionally, a correlation was observed between years of work in the service and compliance in the transfer phase (rho= -0.30, p=0.048). Discussion: Overall compliance was low, which corroborates the stated hypothesis and is similar to other studies described in the literature. Conclusions: The overall compliance to the checklist was very low, with differential behaviors as the surgical instrument technicians showed the highest compliance and the nursing staff the lowest. The antibiotic prophylaxis item was the least compliant, while the pre-anesthesia phase was the most compliant.How to cite this article: Sepúlveda Plata Martha Cecilia. López Romero Luis Alberto.  González Sandra Beatriz. Cumplimiento de la lista de verificación de seguridad de la cirugía en un hospital de Santander. Un estudio de corte trasversal. Revista Cuidarte. 2021;12(3):e2122. http://dx.doi.org/10.15649/cuidarte.2122
Keywords: Compliance; Quality of Health Care; checklist; Incidents; Surgery; Patient Safety